Acids and deep eutectic solvents as novel catalysts for the processing of low grade palm oil for biofuel production / Adeeb Hayyan Alrazzouk - Adeeb Hayyan, Alrazzouk (2015)
This study introduces three new raw materials for biodiesel production, namely acidic crude palm oil (ACPO), low-grade crude palm oil (LGCPO) and mixed industrial palm oil (MIPO). MIPO which is a mixture of low-grade industrial oils, such as ACPO mixed with sludge palm oil (SPO). These raw materials can be characterized in terms of their fatty acid composition and physical properties. They have a similar content of saturated and unsaturated fatty acids. The molecular weight range of raw materials based palm oil is 816-836 (g/mol). Characterization of the abovementioned raw materials showed that they are non-edible and they can be considered as low-grade oils. A pre-treatment process is necessary to convert the free fatty acid (FFA) into fatty acid methyl ester before proceeding with biodiesel production. The development of a catalyst can be considered as a major contribution in the pre-treatment for biodiesel processing. Different types of acids were screened and the following homogenous acids were selected for further optimization: ethanesulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, benzenesulfonic acid, (1R)-(-)-camphor-10-sulfonic acid, 1-propanesulfonic acid and chromosulfuric acid. The optimum conditions for all catalysts are approximately the same in terms of methanol loading, reaction temperature and reaction time, except for the catalyst dosage. Stronger acids require dosages ranging from 0.75%wt (catalyst to oil) to 1% while weaker organic acids need double the dosages to reduce the FFA content to acceptable level. Acids with fluorine atoms, such as trifluoromethanesulfonic acid are not recommended to be used in the biodiesel industry due to safety issues as well as unwanted reactions with air. As, under normal conditions, benzenesulfonic acid is in solid form and (1R)-(-)-camphor-10-sulfonic acid is in powdered form, they are highly recommended. All tested acids were recycled and their activity was studied under optimum conditions. This study revealed that all the acids tested can be recycled at least three times and, further, (1R)-(-)-camphor-10-sulfonic acid and 1-propanesulfonic acid can be utilised six times. Using chromosulfuric acid to compare the efficiency between chemical reactor and sonoreactor, it can be concluded that the esterification reaction is 12 times faster in the former. However, the advantage in using the sonoreactor is that it can handle high FFA content up to 20% but the catalyst dosage, such as sulfuric acid, must be as high as 2%. Conversion of hygroscopic organic acids such as p-toluenesulfonic acid monohydrate (PTSA) into deep eutectic solvent (DES) provides opportunity in the improvement of the esterification reaction, whereby a DES is synthesized by simply mixing a hydrogen bond donor with a salt. Three DESs based on PTSA using ammonium and phosphonium salts were investigated, and it was found that the ammonium-based DES has a higher catalytic activity. The hygroscopicity and the recyclability of DESs were improved, hence indicating their superiority over the heterogeneous acids. Through well established analysis, the biodiesel produced utilizing the different types of catalyst met the EN 14214 and ASTM D6751 standards.